Bicameralism and Its Consequences for the Internal Organization of Legislatures - Diermeier, Daniel; Myerson, Roger B (American Economic Review, 1999)
Theories of organization of legislatures have mainly focused on the U.S. Congress, explaining why committee systems emerge there, but not explaining variance in organization across legislatures of different countries. To analyze the effects of different constitutional features on the internal organization of legislatures, we adopt a vote-buying model and consider the incentives to delegate decision rights in a game among legislative chambers. We show how presidential veto power and bicameral separation can encourage a legislative chamber to create internal veto players or supermajority rules, while a unicameral structure can encourage legislators to delegate power to a leader. (JEL D72)